Household Food Insecurity is Associated with Undernutrition among Primary School Children in Aden Governorate, Yemen - Ahmed Esmail, Shadha Anwar; Rajikan, Roslee (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2021)
Food insecurity is typically linked with undernutrition. However, there is little published data available on the association between household food insecurity and undernutrition status of the primary school children aged 6–12 years in Aden, Yemen. The purpose of this research was to analyse the association between household food insecurity and the undernutrition status of the children. A cross-sectional study was carried out among primary school children from grades I to VI in the government schools (n=525). A simple questionnaire, face-to-face interview with parents, and Radimer/Cornell hunger and food insecurity tool were utilized for the data collection. Anthropometric measurements (weight & height) of the children were also recorded. Upon analysis, 70% of the surveyed children came from a food secure household, whilst 30% experienced some type of food insecurity. Education level of the father (p<0.03), employment of the mother (p<0.00), overall household income (p<0.01), income per capita (p<0.01) and number of working persons per household (p<0.00) were all significant variables associated with food insecurity among these households. Results also showed that the frequency of underweight, stunting and wasting among the children was 19%, 17% and 10%, respectively. Significant associations were found between household food insecurity and the state of being underweight, stunting and wasting. Importantly, the association between household food insecurity and undernutrition status continued even after adjustment for significant variables. In conclusion, household food insecurity was significantly associated with undernutrition status of the primary school children in Aden’s Governorate, Yemen.